Expression of the tetrahydrofolate‐dependent nitric oxide synthase from the green alga Ostreococcus tauri increases tolerance to abiotic stresses and influences stomatal development in Arabidopsis. (June 2015) - Foresi, Noelia; Mayta, Martín L.; Lodeyro, Anabella F.; Scuffi, Denise; Correa‐Aragunde, Natalia; García‐Mata, Carlos; Casalongué, Claudia; Carrillo, Néstor; Lamattina, Lorenzo
Summary: Nitric oxide (NO) is a signaling molecule with diverse biological functions in plants. NO plays a crucial role in growth and development, from germination to senescence, and is also involved in plant responses to biotic and abiotic stresses. In animals, NO is synthesized by well‐described nitric oxide synthase (NOS) enzymes. NOS activity has also been detected in higher plants, but no gene encoding an NOS protein, or the enzymes required for synthesis of tetrahydrobiopterin, an essential cofactor of mammalian NOS activity, have been identified so far. Recently, an NOS gene from the unicellular marine alga Ostreococcus tauri ( OtNOS ) has been discovered and characterized. Arabidopsis thaliana plants were transformed with OtNOS under the control of the inducible short promoter fragment ( SPF ) of the sunflower ( Helianthus annuus ) Hahb‐4 gene, which responds to abiotic stresses and abscisic acid. Transgenic plants expressing OtNOS accumulated higher NO concentrations compared with siblings transformed with the empty vector, and displayed enhanced salt, drought and oxidative stress tolerance. Moreover, transgenic OtNOS lines exhibited increased stomatal development compared with plants transformed with the empty vector. Both in vitro and in vivo experiments indicate that OtNOS, unlike mammalian NOS, efficiently uses tetrahydrofolate as a cofactor in Arabidopsis plants. The modulation of NO production to alleviate abiotic stress disturbances in higher plants highlights the potential of genetic manipulation to influence NO metabolism as a tool to improve plant fitness under adverse growth conditions. Significance Statement: Transgenic Arabidopsis plants expressing nitric oxide synthase from Ostreococcus tauri (OtNOS) accumulate high NO concentration and show increased tolerance to salt, drought and oxidative stress. Transgenic OtNOS lines exhibited increased stomatal index and survival rate to desiccation. OtNOS, unlike mammalian NOS, can efficiently use tetrahydrofolate (THF) as cofactor in Arabidopsis plants. This finding identifies THF as the cofactor employed by the enzymatic system responsible for the arginine‐dependent NO synthesis in higher plants.